Of shrimps and spirits possession : toward a political ecology of resource management in northern Madagascar. - Gezon, Lisa L. (American Antropological Association, 1999)
I present a case of ntual innovation and spirit possession in northern Madagascar that builds on Rappaport's interests in the systemic nature of human-environmental interactions, the relationship between the various levels of political scale, and the interaction between meaning and material relations. I go beyond his formulations in questioning concepts of homeostasis and dynamic equilibrium, and instead propose to understand perturbations as inherent in a system and a source of systemic transformation. In this analysis, I place ecological relations and ritual within an explicitly political framework and examine the processes of social and material change. In drawing on the concept of cognized models, I also illustrate how historical memory and ritual enactments provide ideological frameworks for negotiating control over the use and management of the environment